Idea Penafsiran Semula Al-Qur’an menurut Nasr Hamid Abu Zayd: Suatu Pengamatan Kritis: Reinterpretation of Al-Qur’an by Nasr Hamid Abu Zayd: A Critical Study - Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Al-Qur’an is composed of the Arabic words and the meaning that can be understood through a reliable scientific method. However, the autonomy of this method is to be confused by the idea of ​​reinterpretation of the Qur’an by Nasr Hamid Abu Zayd. Based on the criticisms on the concept of eternity of kalam (God’s word) by Asha`irah, he claims that the meaning of the Qur’anic word is always in the process of renewal. This article aims to analyze the impact of the Quran’s reinterpretation idea from Nasr perspective based on Islamic Thoughts. The methodology used is based descriptively and critically on the process of collecting and analyzing data on the work of related figures. The study found that Nasr was trying to popularize the Muktazilah’s perspective on the status of Quranic createdness as an alternative to Asha`irah’s authoritative perspective. He attempts to describe the restructuring of the Qur’an as a process of communication of God with human through the medium of ‘language’. Through reconception of the aspects of asbab al-nuzul based on the philosophy of historical materialism, Nasr argues that the Qur’an is regarded as a product of human culture influenced by ever-changing social reality. As a result, Nasr advocated the reinterpretation of the Qur’an which was more relevant to the current situation without limitation to the classical interpretation method. Consequently, the understanding of the Qur’an is exposed to the imagination of reason and the philosophical speculation that will undermine the legitimate significance that is indicated and demonstrated by the holy Qur’an.